Out of harm's way? Illicit drug use, medicalization and the law - Shiner, Michael (The British journal of criminology, 2003)
Although British drugs policy has become increasingly contested, debate in this area has continued along well-established lines. Recent reviews, including those conducted by the independent inquiry into the Misuse of Drugs Act and the Select Committee on Home Affairs, have called for reform largely on the basis of the established medicalized philosophy. While the related notions of dangerousness and harmfulness have produced a strong emphasis on control and law enforcement, little attention has been given to the extent to which they provide an appropriate basis for policy. In this article a social classification of illicit drug use is developed and comparisons are made with existing medico-legal classifications. Considerable congruence is evident between these approaches and it is argued that social dimensions of drug use reinforce recent calls for a shift away from enforcement-led approaches, including downgrading the legal classification of cannabis, ecstasy and LSD. However, while social dimensions broadly support the conclusions of the independent inquiry they also highlight the need for more wide-ranging reform. In particular, they suggest that the process of reclassification should be extended to include magic mushrooms and more controversially, perhaps, cocaine